Superação de cláusulas pétreas: uma análise através da linguagem e da mutação constitucional - Ferreira, Carla Rodrigues (2007)
The present research’s finality is to investigate the possibility of the petrified clauses’ overrule. For this, it recurs initially to the analysis of the language and of the informal mechanisms of alteration of the Constitution. The research, in attention to the Semiotics (the General Theory of the Signs), observes its three levels: the syntactic, the semantic and the pragmatic, as well as the different levels of language, to properly relate them to the Juridical Science. Also asseverates that the law system is constituted by the language, and that it works with the language all the time, since it recurs, always, to the interpretation of the language’s principles. Of the concept of the juridical norms, captures the idea that they consubstantiate in the prescriptive propositions, in such a way that they are extracted from the legal text by the interpreter. With the intent to enter in the discussion’s core, the research discourses about the constitutional mutation by interpretation, which consists in a process of informal change of the Constitution that modifies the meaning of its text, but letting it formally untouched. Emphasizing the investigation about the constitutional mutation by the judicial interpretation of the Constitution, observes that the judges and Courts, when applying the Constitution, create rights (once the jurisdictional activity is enunciation), for the juridical norm is the proposition, the idea generated in the human mind by the legal text, and not the legal text itself. In this way, we can conclude that the petrified clauses can be analyzed as legal text, configuring truly insurmountable obstacles to the reforming power; and as propositions, in which case they can be overruled, as long as the interpreter respects the inner elasticity of the normative text and do not affronts the spirit of the Constitution. In order to accomplish that, it’s only necessary to give new signification to the Constitution’s enunciations, adjusting them to the needs and the aspirations of the society.